Misunderstandings and Difficulties in Making Sense of the Action - Rivero-Obra, Mercedes (Problemos, 2024)
Traditionally, intelligibility is associated with rationality. It is also associated with the meaning and understanding of the agent’s actions when interacting in a context. What is proposed in this work is an analysis – at the moment in which the agent is interacting – of what happens when intelligibility and meaning are decoupled. It causes a person’s actions to be misunderstood or misinterpreted by others. It is even possible that the same person will not understand, later, why she has acted the way she has. The explanation proposed is that this link is broken when the action process, made up of the three stages of action, is not developed correctly. This results in misunderstandings that, because they are directly related to the action, I have called misunderstandings within agency. The analysis of this kind of misunderstanding could be essential to understanding the conflicts that arise in the communicative act and mutual understanding.
Keywords: Agency; Intelligibility; Misunderstanding; Rationality; Meaning-giving